A Na+/K+ ATPase Pump Regulates Chondrocyte Differentiation and Bone Length Variation in Mice - Marchini, Marta; Ashkin, Mitchell R.; Bellini, Melina; Sun, Margaret Man-Ger; Workentine, Matthew Lloyd; Okuyan, Hamza Malik; Krawetz, Roman; Beier, Frank; Rolian, Campbell (Frontiers in Cell and Developmental Biology, 2021)
The genetic and developmental mechanisms involved in limb formation are relatively well documented, but how these mechanisms are modulated by changes in chondrocyte physiology to produce differences in limb bone length remains unclear. Here, we used high throughput RNA sequencing (RNAseq) to probe the developmental genetic basis of variation in limb bone length in Longshanks, a mouse model of experimental evolution. We find that increased tibia length in Longshanks is associated with altered expression of a few key endochondral ossification genes such as Npr3, Dlk1, Sox9, and Sfrp1, as well reduced expression of Fxyd2, a facultative subunit of the cell membrane-bound Na+/K+ ATPase pump (NKA). Next, using murine tibia and cell cultures, we show a dynamic role for NKA in chondrocyte differentiation and in bone length regulation. Specifically, we show that pharmacological inhibition of NKA disrupts chondrocyte differentiation, by upregulating expression of mesenchymal stem cell markers (Prrx1, Serpina3n), downregulation of chondrogenesis marker Sox9, and altered expression of extracellular matrix genes (e.g., collagens) associated with proliferative and hypertrophic chondrocytes. Together, Longshanks and in vitro data suggest a broader developmental and evolutionary role of NKA in regulating limb length diversity.